Richardson, Ridley, and Tatís Jr. Versus The Public: A Rhetorical Analysis of Athlete Self-Defense Rhetoric and Public Response - (:unkn) unknown (My University, 2024)
This project addresses issues brought forth by critical race theory through analysis of three marginalized athletes’ rhetorical response to accusations of wrongdoing on social media, as well as how members of the public receive the athletes’ self-defense rhetoric and identities. Through three case studies, I utilize apologia theory and tenets of image restoration theory to give meaning to how Sha’Carri Richardson, Calvin Ridley, and Fernando Tatís Jr. respond to accusation. In response, I analyze how members of the public attend to issues brought forth by critical race theory through their exhibition of color-blind racism and/or rhetorics of whiteness. In the first case study, Richardson exhibits self-defense tools to present herself as a victim of her circumstances, while also positively framing her characteristics and career. In response, individuals mostly support the athlete, however, others reinforce existing stereotypes about Black women. In the second case study, Ridley attempts to appear relatable and connect with his audience through discussion of his mental health. In response, members of the public are mostly supportive, but others uphold ideologies about hegemonic masculinity and beliefs surrounding Black men’s mental health. In the final case study, Tatís Jr. exhibits tactics that contradicted one another, resulting in a majority of individuals exhibiting racialized rhetorics, reinforcing racial stereotypes. This project concludes with review of the differences between athletes, the need for critical race theory, limitations, and future direction for my project.
Keywords: Apologia; Color-blind Racism; Public Response; Rhetorical Analysis; Rhetorics of Whiteness; Self-Defense